An experimental study on the flexural behaviour of FRP RC bemas and comparison of the ultimate moment capacity with ACI - Chitsazan, I.; Kobraei, M.; Jumaat, Mohd Zamin; Shafigh, P. (Journal of Civil Engineering and Construction Technology, 2010)
As it is known, fiber reinforced polymer (FRP) bars are typically quite different from those of steel bars and they depend mainly on both matrix and fibers type, as well as on their volume fraction; although generally, FRP bars have lower weight, lower modulus of elasticity, but higher strength than steel. In the other hand, FRP has disadvantages, for instance: no yielding before brittle rupture and low transverse strength. In this research, we have investigated flexural behavior in reinforced concrete beams with glass fiber-reinforced polymer (GFRP) and have analyzed the different kinds of failure, ultimate moment capacity, deflection, load of first crack, how to create and expand cracks, tensile and compressive strains created on beam and position of neutral axis (NA) during loading for different ratios of bars on 10 laboratorial specimens. Using high strength concrete instead of normal concrete and increasing the effective depth over the breadth on flexural behavior of concrete beams with GFRP had been studied. Results taken from the experimental tests have been compared with ACI 440 and they show that deflections, width of cracks and the cracksâ extent are further used toward the usual RC beams. High strength concrete instead of normal concrete is the ascended load of the first crack and it created more cracks, but with less width of crack. It is recommended that the selected ratio of effective depth over breadth (d/b) is slightly larger than 2. In addition, it can be said that the amount of the balanced bar provided by ACI 400 is not an exact criteria to determine the type of failure, and it is only in cases where the ratio of bars are lower than the balanced mode that ruptures occur in reinforcement area.